1981
DOI: 10.1007/bf00264983
|View full text |Cite
|
Sign up to set email alerts
|

Translocations induced by fast neutrons and X-rays in Delia antiqua

Abstract: A comparison was made using X-rays and fast neutrons for the induction of translocations in Delia antiqua. Using the same radiation dose, no difference in efficiency between the two radiation types could be observed. However, with fast neutrons many multiple translocations were induced, including a quadruple translocation involving 4 out of 5 autosomes. One male linked translocation was also induced.The reciprocal translocations were assigned into two classes: symmetrical and asymmetrical, and ten of the latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The overall frequency of translocation induction was 892 per cent which agrees well with equivalent data when normal males are irradiated (Robinson and Van Heemert, 1980a). However, what is different is the proportion of the translocation which was Y-linked, 18 per cent, a frequency which agrees very well with the expectation based on chromosome length (21 per cent) of the Y-2 translocation complex.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The overall frequency of translocation induction was 892 per cent which agrees well with equivalent data when normal males are irradiated (Robinson and Van Heemert, 1980a). However, what is different is the proportion of the translocation which was Y-linked, 18 per cent, a frequency which agrees very well with the expectation based on chromosome length (21 per cent) of the Y-2 translocation complex.…”
Section: Resultssupporting
confidence: 83%
“…The F1 males (Dd) were mass-mated with dd females and the sterilities of these females is illustrated in fig. 2; it is very similar to that recorded when normal males were irradiated with 200 rads of fast neutrons (Robinson and Van Heemert, 1980a). Out of 807 separated females 695 (86 per cent) showed no clear increase in sterility and were discarded.…”
Section: Resultssupporting
confidence: 74%
“…It is recommended that the default dose of 400 Gy of X-ray or gamma ray was recently approved as a disinfestation treatment for stored product insects other than lepidopteran species, the lethal dose in lepidopteran species might be more than 400 Gy (FAO, 2003;Hallman, 2013), the Indian meal moth P. interpunctella is one of the most radio tolerant insect known, which need a dose more than 600 Gy of gamma ray to prevent its reproduction (Hallman, 2000(Hallman, , 2013. It was reported that the FNI was more effective in producing lethality and sterility than gamma and X-rays (Offori & Czock, 1971;Glenn & Ducoff, 1976;Robinson & Van Heemert, 1981). Regarding a high penetration of FNI, it might be more effective for using in the disinfestation treatment and SIT much more than other form of irradiations.…”
Section: Discussionmentioning
confidence: 99%
“…In T4 with a significant deviation of the NN/TN ratio only a few TT individuals were observed, although a large number of larvae were analysed (247). In translocations T6, T33, T42 and T52 the TT larvae were relatively fit and in three of these stocks viable TT adults were observed (Robinson & Van Heemert, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In several other species such unbalanced duplication karyotypes have been observed (Aslamkhan & Aaqil, 1970;Curtis et al, 1972;Dennh6fer, 1974;La Chance et al, 1977;Sakai et al, 1971 andVed Brat &Rai, 1974) resulting in some cases in a higher egg hatch compared to the stocks which gave no duplication larvae. It should be kept in mind that translocations with such viable 'duplication' karyotypes have severe disadvantages for genetic control purposes where the larval stage does the damage (Robinson, 1976;Robinson &Van Heemert, 1981 andVan Heemert, 1980).…”
Section: Discussionmentioning
confidence: 99%